Complications of Diabetes Mellitus - A Pathologic Overview - Arzoo Alagh; Samarth Shukla (A Concise Clinicopathological Handbook of Diabetes Mellitus, 2021)
The complications of diabetes mellitus includes microaangiopathy, macroangiopathy, retinopathy, nephropathy and neuropathy. Many studies have concluded that complications are nothing but the consequences of metabolic dysfunction. The late systematic complications of diabetes are the major causes for its morbidity and mortality. Diabetic patients have a two to four folds higher frequency of coronary artery diseases, and a four times greater threat of dying from cardiovascular complexities than non-diabetic patients. Also, Kidneys are prime targets of diabetes causing diabetes nephropathy. In long standing diabetes, it usually affects the peripheral nerves, brain and spinal cord.